The Effectiveness of The Addition of Slow Deep Breathing to Brain Gym Exercise on Cognitive Impairment of The Elderly - Maharani, Dhia, Ms; Ali, Mohammad, Mr; Sativani, Zahra, Mrs (UI Scholars Hub, 2025)
Background: According to WHO, 65.5 million elderly people worldwide have impaired cognitive function. Cognitive impairment can be caused by impaired oxygen supply to the brain, stress, and lack of physical activity. Physiotherapy has a role in elderly cognition through interventions to improve cognition, namely in the form of Brain Gym Exercise with the addition of Slow Deep Breathing. Objective: Knowing the effectiveness of the addition of Slow Deep Breathing to Brain Gym Exercise on cognitive impairment of the elderly at Panti Sosial Tresna Werdha Budi Mulia 4. Methods: This study used quasi experimental with two group pre-post test design. Sampling with purposive sampling amounted to 22 respondents. The measuring instrument uses the Mini Mental State Examination (MMSE). Treatment group 1 was given Brain Gym Exercise with Slow Deep Breathing and treatment 2 was given Brain Gym Exercise. Results: Paired sample t test results in treatment group 1 found delta mean 7.91 and p value 0.000. While in treatment group 2, the delta mean was found to be 3.00 and p value 0.000. In the independent sample t test, the comparison between treatment group 1 and treatment group 2 obtained a p value of 0.000. Conclusion: The provision of Brain Gym Exercise intervention with the addition of Slow Deep Breathing has a more significant effect on the elderly with cognitive impairment than just the Brain Gym Exercise intervention alone.